Gastroduodenal Ulcerative Colitis in Association with Ulcerative Pancolitis - Khin San Aye; Lin Lin Htun; Thet Mar Win; Mya Thida Aye; Drmyothettin Tin; Than Than Aye (Case Reports in Gastrointestinal Medicine)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease, traditionally regarded as being limited to the colorectum. Although several gastroduodenal lesions have been reported in cases of UC, in general, duodenal lesions in UC are believed to be uncommon and gastric lesions in UC are a rare presentation. In this report, we presented a 66-year-old lady with upper GI presentation with gastroduodenal ulcerative colitis accompanying pancolonic UC.